2009
DOI: 10.2190/ag.68.4.d
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Responses to Conflict in the Workplace

Abstract: Socioemotional selectivity theory (SST) has been used successfully to explain age differences in interpersonal conflict behavior: older adults are generally less likely to engage in destructive responses, and more likely to employ nonconfrontational ones. However, this research has focused almost exclusively on conflict with intimates (spouses, family, friends), and has typically not examined conflict in the workplace. The present investigation uses behavior ratings made by bosses, peers, and subordinates of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 30 publications
9
57
2
Order By: Relevance
“…The interaction patterns between age and contract breach revealed that in cases of serious contract breach, in particular, job satisfaction and job performance of younger workers became lower than those of older workers. A possible explanation is that older workers are able to buffer the negative effects of contract breach by regulating their emotions in a constructive way (Davis et al., ; Ng & Feldman, ). Even though contract breaches may be strongly related to changes in job satisfaction and job performance, older workers' job satisfaction and job performance are less influenced by contract breaches than younger workers'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction patterns between age and contract breach revealed that in cases of serious contract breach, in particular, job satisfaction and job performance of younger workers became lower than those of older workers. A possible explanation is that older workers are able to buffer the negative effects of contract breach by regulating their emotions in a constructive way (Davis et al., ; Ng & Feldman, ). Even though contract breaches may be strongly related to changes in job satisfaction and job performance, older workers' job satisfaction and job performance are less influenced by contract breaches than younger workers'.…”
Section: Discussionmentioning
confidence: 99%
“…Socio‐emotional selectivity theory (Carstensen, ; Carstensen & Mikels, ) and the model of emotion regulation (Gross, , ; Gross, Carstensen, Pasupathi, Tsai, Skorpen, & Hsu, ; John & Gross, ) have been used extensively in understanding how older people differ from younger people in motivation and behavior, as well as in explaining the impact of age on work behaviors (see e.g. Davis, Kraus, & Copabianco, ; Kooij, De Lange, Jansen, Kanfer, & Dikkers, ; Ng & Feldman, ).…”
Section: Introductionmentioning
confidence: 99%
“…, but has rarely been tested in an actual work setting (cf. for few exceptions Cate & John, 2007;Davis, Kraus, & Capobianco;Zacher & Frese, 2009), and never in relation to intrinsic work motivation. According to Carstensen, Isaacowitz, and Charles (1999), the perception of reaching retirement contributes to making experiences more positive.…”
Section: The Role Of Time Perspectivementioning
confidence: 98%
“…Younger adults tend to prefer knowledge‐related goals because knowledge acquisition, career prospects and social network are more important to them. Therefore, older adults are more likely to utilise non‐confrontational approaches, such as yielding and delaying responding, than their younger counterparts when dealing with work conflict (Davis, Kraus, & Capobianco, ). These findings suggest that age may influence the relationship between social identity salience, motivational orientation and conflict strategies.…”
Section: Dual Concern Modelmentioning
confidence: 99%